2020
DOI: 10.2478/rjr-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Nasal swell body: a literature review

Abstract: The nasal swell body (NSB) is considered to be an enlarged region of the nasal septum, which is located superiorly to the inferior nasal turbinate and anteriorly to the middle nasal turbinate, with a potential effect upon the airflow nasal valve. The histological studies of the NSB demonstrated that it is a glandular formation, not a venous structure, and it is formed by septal cartilage and bone, as well as a thick mucosa. Recent studies emphasized the functional role of the nasal swell body and it is thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[22][23][24][25][26] Several studies have shown that nasal RF thermal ablation is a safe and effective method for reducing submucosal tissue associated with NAO while preserving mucosal function. [27][28][29] The unique characteristics of the SSB tissue as well as the structure's location within the nasal airflow pathway underscore the importance of considering the SSB as a contributor for patients with obstructed nasal airflow. 13,29 Similar in composition and function to the IT, the dynamic TA B L E 3 Adverse events reported with a relationship to the study device or procedure by patient (n = 9) a .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24][25][26] Several studies have shown that nasal RF thermal ablation is a safe and effective method for reducing submucosal tissue associated with NAO while preserving mucosal function. [27][28][29] The unique characteristics of the SSB tissue as well as the structure's location within the nasal airflow pathway underscore the importance of considering the SSB as a contributor for patients with obstructed nasal airflow. 13,29 Similar in composition and function to the IT, the dynamic TA B L E 3 Adverse events reported with a relationship to the study device or procedure by patient (n = 9) a .…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] The unique characteristics of the SSB tissue as well as the structure's location within the nasal airflow pathway underscore the importance of considering the SSB as a contributor for patients with obstructed nasal airflow. 13,29 Similar in composition and function to the IT, the dynamic TA B L E 3 Adverse events reported with a relationship to the study device or procedure by patient (n = 9) a . nature and compensatory features of the SSB and their role in NAO are becoming more fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation